Anticancer Evaluation of Plants from Indonesian Tropical Rain Forests - Jamilah Abbas (Indonesian Journal of Cancer Chemoprevention, 2011)
The anticancer activities of medicinal plants from Indonesia’s tropical rainforests were investigated against Hela cell line. Maytenfoliol from leaves of Calophyllumtetrapterum 3-epibetulinic acid from stem bark of C. tomentosum Wight and D.A-friedo-oleanan-3-on from stem bark of C. moonii showed anticancer activity. The compound 3-epibetulinic acid showed the more potent anticancer activity than maytenfoliol and D.A-friedo-oleanan-3- with thean IC50 value were 3.17 μg/mL, 4.89 μg/mL and 5.63 μg/mL, respectively.Keywords: Anticancer evaluation, Hela cell line, Calophyllumtetrapterum. C. tomentosum Wight and C. moonii